ANTICANCER ACTIVITY OF BANANA FLOUR EXTRACTS ON COLORECTAL CANCER CELLS - Phimsen, Suchada; Jannoey, Panatda; Boonsong, Tantip; Meemuk, Wannapha; Thalapphet , Donruetai; Kijchalao, Nutthamon (Life Sciences and Environment Journal, 2023)
This study was aimed to investigate the anticancer effect of banana flour extracted with different solvents (ethanol, methanol, hexane and water) against colorectal cancer HCT116 and SW480 cell lines. Cell viability and cell death were determined by MTT and trypan blue dye exclusion assay. Apoptosis was investigated by western blot analysis and Hoechst 33342 staining. The results found that ethanolic banana flour extract (eBFE) inhibited cell viability of HCT116 and SW480 greater than other solvent extracts. The eBFE was able to significantly inhibit cell proliferation by dose and time dependent manners. According to the IC50 values, eBFE had a greater anti-proliferative effect on HCT116 than SW480 cells. In addition, eBFE induced cell death and apoptosis by proteolytic activation of caspase-3 and the appearance of chromatin condensation. Collectively, the crude extract of eBFE contains active components that exert growth inhibition in colorectal cancer. This study suggested that banana flour had the potential for cancer prevention and therapy.